Northam River Bridge, Southampton, UK: a life-extension maintenance project. Issue 4 (13th August 2019) - Simpkins, John; Cole, Graham
Abstract : The Northam River Bridge in Southampton, UK, carries the A3024 principal road across the River Itchen. The 1954 structure was a pioneer of early concrete post-tensioning techniques, with longitudinal prestressed beams held together both transversely and longitudinally with transverse post-tensioning. Works started in 2014 to address extensive water seepage that was potentially corroding post-tensioning elements. The need to avoid traffic disruption was a significant constraint in delivering the scheme. A post-tensioned special inspection to vulnerable details was undertaken when the main works contract started and a contraflow system was introduced. This revealed issues with the transverse tensioning that implied a need for reassessment. The outcome was that the majority of the structural elements were suitable for 40 t assessment live loading. However, there was a further requirement for measures to prevent any accidental wheel loading to the edge beams.